And now I become its mouth: On Arthur Schopenhauer and weird ventriloquism. Issue 1 (1st June 2019) - Zager, Brian
From Arthur Schopenhauer we can glean a characteristically moody perspective on the primordial condition of speaking and being spoken. Focusing on his dualistic view of the embodied subject as having to contend with the forces of both Will and presentation, in this article I argue that his philosophy construes communication as a sort of weird ventriloquism. Drawing on François Cooren's proposed method of 'ventriloqual analysis', I re-examine Schopenhauer's subject as a being that both animates and is animated by his strange dark noumena. Bearing witness to this eerie metaphysical stagecraft, his concept of Will becomes synonymous with a will to communicate, which manifests itself through the voice of the speech actor and allows us to think about his ontology and ethics from a different rhetorical perspective.